Chloride Ion Removal from the Wet Flue Gas Desulfurization and Denitrification Wastewater Using Friedel’s Salt Precipitation Method - Ping Fang; Zi-jun Tang; Xiong-bo Chen; Jian-hang Huang; Zhi-xiong Tang; Chao-ping Cen (Journal of Chemistry)
The desulfurization and denitrification wastewater (DDW) from the wet flue gas treatment project is difficult to be treated and recycled because of high chloride ion (Cl−) concentration. Cl− can cause equipment and piping corrosion. However, there is a lack of cost-effective treatment technologies for the removal of Cl− from the DDW. In this research, the feasibility of Cl− removal from the DDW using Friedel’s salt precipitation method was evaluated. Factors affecting the Cl− removal, such as Ca(OH)2 dosage, NaAlO2 dosage, solution’s initial pH, solution’s temperature, reaction time, stirring speed, and anions (SO42−, NO3−, and F−), were investigated, and the optimal experimental conditions for Cl− removal were determined. Experimental results showed that Friedel’s salt precipitation method can remove Cl− effectively and can achieve synergistic removal of SO42−, F−, and heavy metal ions. Under the best experimental conditions, the average removal efficiencies of Cl−, SO42−, F−, and heavy metal ions reach more than 85%, 98%, 94%, and 99%, respectively. The Cl− removal mechanism studies showed that Cl− can be removed by precipitation as Ca4Al2Cl2(OH)12. The purified wastewater and the precipitated solid can be reused to reduce the consumption of water and alkali. Friedel’s salt precipitation method is an effective control technology for the synergistic removal of Cl−, SO42−, F−, and heavy metal ions and has enormous potential to be applied in the industrial wastewater treatment field.